Production of ethanol by immobilized saccharomyces cerevisiae - Noordiana , Ariffin (2015)
This research was conducted on the fermentation of ethanol by Saccharomyces cerevisiae using immobilization technique. S. cerevisiae which is also known as Baker’s yeast is a single-celled eukaryote that is frequently used in scientific research. It is an attractive model organism due to the fact that its genome has been sequenced, its genetics are easily manipulated and very easy to maintain in the laboratory. Besides, immobilization has already been approved as useful method in maintaining high cell concentration within the reactor, increases the cell’s ability to tolerate high ethanol concentration in the medium, allowing higher conversion yield and increased volumetric productivities. Therefore, the purpose of this study is to immobilize the yeast using various kind of supports (e.g: muslin cloth, membrane and sugarcane stalk) in batch processes to determine the best support for ethanol production. In this method, immobilized fermentation was carried out through shake flask seeding technique while the duration of fermentation process was fixed at 10 hours with sampling made at every 2 hours intervals. The germination of the stock and seed culture preparations were conducted followed by the immobilization technique in order to produce ethanol. Samples taken were analyzed for ethanol and glucose concentration, colony forming unit (CFU), biomass concentration, optical density and viewing of S. cerevisiae attachment on immobilized supports by Scanning Electron Microscope (SEM). From the result obtained, it showed that immobilized cloth was capable to increase cell optical density up to 1.602 after 10 hours of fermentation. Moreover, analysis performed by using biomass has revealed that immobilized cloth at 10 hours of fermentation gave the highest biomass concentration which is 39.64 gL-1 and colonies of cells forming at 2.57 x 108/mL of viable cells compared to other materials. Besides, its ethanol productivity was enhanced to 0.42 gL-1h-1, being over 9.6% higher than that observed in the batch culture (0.38 gL-1h-1). The consumption of glucose was improved by 6.9% (compared to batch operation), where nearly 67% of glucose conversion at 10 hours period of immobilized fermentation through muslin cloth. The increment might be associated with the altered metabolical functions in the immobilized cells. This alteration is attributed to the reduction of the diffusion path of the growth nutrient that enhanced the availability and promoted the growth of yeast, thus improving the catalytic conversion of glucose to ethanol. Therefore, the supported muslin cloth was proved to increase the number of cells and glucose inhibition is able to reduce with the utilization of immobilized S. cerevisiae, thus increasing ethanol production